KEMAMPUAN MANAJERIAL, DAN BUDAYA ORGANISASI TERHADAP KINERJA DOSEN DI LINGKUNGAN IAIN BENGKULU - Zulkarnain S (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
This means that good personality results in improved lecturer performance. Managerial ability has a positive direct effect on performance. This means that  good managerial skills lead  to improved lecturer performance. Organi- zational culture has  a direct positive effect on performance. This means that  a good  organizational culture, resulting in improved lecturer performance. Personality has a direct positive effect on organizational culture. This means that  a good personality leads to an increase in organizational culture. Managerial ability has a direct positive effect on organi- zational culture. This means that good managerial skills, resulting in increased organizational culture